A new tephrochronology for early diverse stone tool technologies and long-distance raw material transport in the Middle to Late Pleistocene Kapthurin Formation, East Africa. Issue 121 (August 2018) - Blegen, Nick; Jicha, Brian R.; McBrearty, Sally
Abstract: The Middle to Late Pleistocene (780–10 ka) of East Africa records evidence of significant behavioral change, early fossils of Homo sapiens, and the dispersals of our species across and out of Africa. Studying human evolution in this time period thus requires an extensive and precise chronology relating behavioral evidence from archaeological sequences to aspects of hominin biology and evidence of past environments from fossils and geological sequences. Tephrochronology provides the chronostratigraphic resolution to achieve this through correlation and dating of volcanic ashes. The tephrochronology of the Kapthurin Formation presented here, based on tephra correlations and 40 Ar/ 39 Ar dates, provides new ages between 395.6 ± 3.5 ka and 465.3 ± 1.0 ka for nine sites showing diverse blade and Levallois methods of core reduction. These are >110 kyr older than previously known in East Africa. New 40 Ar/ 39 Ar dates provide a refined age of 222.5 ± 0.6 ka for early evidence of long-distance (166 km) obsidian transport at the Sibilo School Road Site. A tephra correlation between the Baringo and Victoria basins also provides a new date of ∼100 ka for the Middle Stone Age site of Keraswanin. By providing new and older dates for 11 sites containing several important aspects of hominin behavior and extending the chronology of the Kapthurin Formation forward by ∼130, 000 years, the tephrochronology presented here contributes one of the longest and most refined chronostratigraphic frameworks of Middle through Late Pleistocene East Africa. This tephrochronology thus provides the foundation to understand the process of modern human behavioral evolution as it relates to biological and paleoenvironmental circumstances.